2001
DOI: 10.1016/s0169-8095(00)00098-3
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the international climatology of tornadoes by damage classification

Abstract: Reports of tornadoes, broken down by damage, from seven countries have been examined. In particular, the long-term relatively high-quality dataset from the US is used to develop distributions which indicate that the number of tornadoes decreases log-linearly with increasing F-scale. Two distinct distributions, one apparently associated with supercell tornadogenesis processes and the other with non-supercell processes, are found in both the US data and in other countries. The similarity of the distribution in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 7 publications
3
66
0
3
Order By: Relevance
“…Field surveys have certainly given more accurate data on tornado path lengths. Other factors for a more systematic reporting of weak tornadoes over time (Brooks and Doswell, 2001) include a general improvement of public awareness and increasing urbanization.…”
Section: Datamentioning
confidence: 99%
“…Field surveys have certainly given more accurate data on tornado path lengths. Other factors for a more systematic reporting of weak tornadoes over time (Brooks and Doswell, 2001) include a general improvement of public awareness and increasing urbanization.…”
Section: Datamentioning
confidence: 99%
“…Brooks and Doswell (2001) showed that the distribution of tornadoes by (E)F-scale for the U.S. compared with several other countries 1 is similar for (E)F-3 and higher intensity events. The Weibull distribution has been shown to model observed tornado intensities (Dotzek et al, 2003) as well as path length and width (Brooks, 2003a).…”
Section: Determination Of Threshold For Significant Tornado Eventsmentioning
confidence: 84%
“…34 As observed by Hurst (1951). 35 The dataset for the occurrence was obtained on http://www.spc.noaa.gov/archive/, and the model for losses was obtained from Brooks and Doswell (2001).…”
Section: The Challenge Of Updating Probabilitiesmentioning
confidence: 99%